Aspek Hukum Perlindungan Indikasi Geografis Berbasis Ham - Maria Alfons (Fakultas Hukum Universitas Mataram, 2015)
Law No. 15 of 2001 Trademarkare manage geographical indication on articles 56 to 58 as part of the substance of geographical indications (GI) basically regulate the protection of the products to local communities as a sign that indicates the place of origin of goods is due to human factors, or a combination of both factors, provide specific characteristics and quality of the goods results of the product. Then, the issuance of Government Regulation No. 51 year 2007 on Geographical indications for clearer protect as expected in the TRIPS Regalements. Constitutionally Article 33, paragraph 3 of the 1945 Constitution mentions